2010
DOI: 10.1073/pnas.0913828107
|View full text |Cite
|
Sign up to set email alerts
|

ACAT1 gene ablation increases 24(S)-hydroxycholesterol content in the brain and ameliorates amyloid pathology in mice with AD

Abstract: Cholesterol metabolism has been implicated in the pathogenesis of several neurodegenerative diseases, including the abnormal accumulation of amyloid-β, one of the pathological hallmarks of Alzheimer disease (AD). Acyl-CoA:cholesterol acyltransferases (ACAT1 and ACAT2) are two enzymes that convert free cholesterol to cholesteryl esters. ACAT inhibitors have recently emerged as promising drug candidates for AD therapy. However, how ACAT inhibitors act in the brain has so far remained unclear. Here we show that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
202
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 179 publications
(210 citation statements)
references
References 58 publications
8
202
0
Order By: Relevance
“…Bryleva et al (37) measured the CE content in mouse brains by separating the CE fraction from the free cholesterol fraction using silica column chromatography. They then determined the cholesterol content present in CE by GC/MS after CE was saponified.…”
Section: The Contents Of Ce and 24soh In The Mouse Brainsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bryleva et al (37) measured the CE content in mouse brains by separating the CE fraction from the free cholesterol fraction using silica column chromatography. They then determined the cholesterol content present in CE by GC/MS after CE was saponified.…”
Section: The Contents Of Ce and 24soh In The Mouse Brainsmentioning
confidence: 99%
“…Hudry et al did not observe a reduction in the hAPP protein content; instead, they demonstrated a decrease in hAPP processing by gamma-secretase, an increase in SREBP2 mRNA, and no change in brain cholesterol content. Bryleva et al (37) showed that A12 in 3XTg-AD mice caused a 32% increase in 24SOH content, a modest reduction in cholesterol biosynthesis rate and in brain cholesterol content, and a significant reduction in amyloid pathology. This work implies that a modest increase in 24SOH content can lead to a decrease in the full-length hAPP content.…”
Section: Roles Of Oxysterols In Vivomentioning
confidence: 99%
See 3 more Smart Citations